Effects of long non-coding RNA Gm14461 on pain transmission in trigeminal neuralgia - Mu Xu; Yi Yan; Mengye Zhu; Zhijian Wang; Xuexue Zhang; Daying Zhang (BMC, 2020)
Abstract Background This study aims to investigate the role of long non-coding RNA Gm14461 in regulating pain transmission in trigeminal neuralgia (TN). The mouse TN model was produced by chronic constriction injury of the infraorbital nerve (CCI-ION). The values of mechanical withdrawal threshold (MWT) were measured to assess the nociception of mice at different times after CCI-ION surgery (0, 1, 3, 5, 7, 9, 11, 13, 15 d). The primary mouse trigeminal ganglion neurons (TGNs) were isolated from C57BL/6 J mice and treated with TNF-α to mimic a TN cellular model. The expression of Gm14461, TNF-α, IL-1β, and IL-6 was examined using qRT-PCR. The protein levels of CGRP and P2X3/7 receptor were measured using western blot. Results Gm14461 expression was increased in trigeminal ganglia (TGs) of TN mice on the operation side. Furthermore, Gm14461 knockdown in TGs increased, whereas Gm14461 overexpression decreased MWT in TN mice. Moreover, Gm14461 knockdown downregulated, whereas Gm14461 overexpression upregulated mRNA levels of TNF-α, IL-1β, and IL-6 and protein levels of CGRP and P2X3/7 receptor in TGs from TN mice. In vitro assay showed that Gm14461 was upregulated by TNF-α, IL-1β, and IL-6. Additionally, Gm14461 knockdown decreased protein levels of CGRP and P2X3/7 receptor in TNF-α-treated TGNs, whereas Gm14461 overexpression exerted the opposite effect. Conclusion Gm14461 promoted pain transmission (reduced MWT value) in a CCI-ION-induced mouse TN model. The underlying mechanisms might involve the regulation of pro-inflammatory cytokines, CGRP and P2X3/7 receptor.